Appendiceal Mucocele: Report of a Case and Brief Review - Chakraborty, Debashis; Rahman, SM Mahfuzur; Rahman, SM Tauhidur (Eastern Medical College Journal, 2025)
Appendiceal mucocele (AM) is a lesion of the appendix, characterized by a gross enlargement of the appendix from accumulation of mucoid substance within the lumen. It may be caused by benign or malignant diseases. AM is a rare condition, encountered in only 0.1-0.4% of all appendectomies with a female predominance. Clinically it can remain either asymptomatic for long time or it can manifest with abdominal pain that can be associated with the presence of a palpable mass. The most common clinical manifestation is pain in the right iliac fossa. Preoperative diagnosis is rare, while it is more frequently intraoperative. Therapy is fundamentally surgical. We report the case of a 10-year male with right lower abdominal pain, anorexia and low-grade fever. A complete blood count, urine routine examination and ultrasonogram of the whole abdomen Eastern Med Coll J. July 2025; 10 (1): 81-83